ADAPTABILIDAD DEL PASTO (Andropogon gayanus) EN EL RECINTO LA COOPERATIVA GUASAGANDA - Pilatasig Ante, Adrián Santiago (2017)
The present research project focused on determining the adaptability of A. gayanus in the Guasaganda Cooperative Campus and to know at what age the grass is found to have higher morphometric and nutritional value. We evaluated the plant height, fresh weight, leaf length and width. The nutrients that were evaluated were: Dry matter, protein, ethereal extract, fiber, ash and nitrogen-free extract on fresh and dry basis. The results show that at 75 days of cutting, a greater response is achieved significantly in plant height, fresh weight, leaf length and width; and the lowest values were obtained when the cut was performed at 30 days. Regarding the nutrient composition response in fresh basis of A. gayanus, no significant difference was found in any of the indicators; on the other hand, a difference was found in indicators such as fiber and carbohydrates for analyzes performed on a dry basis for treatment with cut at 75 days and 30 days respectively. From the results obtained in the present investigation, the cut at 75 days provides a better response by the plant.